Measuring the Quality of Bank Regulation and Supervision, with an Application to Transition Economies - Bilin Neyapti; Nergiz Dincer (Turkish Economic Association, 2004)
This study develops a method to evaluate the quality of a legal framework for bank regulation and supervision (RS) by developing an extensive set of criteria and a coding system. Using this method, we generate an original set of measurements for RS by evaluating the letter of banking laws of 23 transition economies. In doing so, we also utilize the Basle guidelines on banking supervision and the related literature. The indices of RS indicate that legal banking reforms in Poland, Hungary and Estonia have been more ambitious than the rest of the countries in transition. In general, however, banking laws in transition economies indicate a lower regulatory and supervisory quality than indicated by the German banking law, if one is willing to choose the latter as a benchmark. This data set permits an empirical analysis of the relationship between legal RS and macroeconomic performance. The empirical evidence in the paper shows a significant positive relationship between RS and real GDP growth in transition economies.
Keywords: E44; G2; K29; 330; Bank regulation and supervision; growth; transition economies